Bilateral trade balance, exchange rates, and income: evidence from Malaysia - Yusoff, Mohammed (The Berkeley Electronic Press, 2009)
This study attempts to examine the effects of real bilateral exchange rates on Malaysia’s bilateral trade balances with its three major trading partners: the USA, Japan, and Singapore. The results suggest that the bilateral trade balance, real exchange rate, domestic and foreign incomes are cointegrated. In the long-run, Malaysia’s bilateral trade balances are found to be responsive to the changes of bilateral exchange rate in the cases of the USA and Singapore but irresponsive for Japan. There is a clear evidence of the J-curve effect only in the case of Malaysia’s trade balance with the United States. The results also indicate that devaluation tends to be recessionary. The findings suggest that Malaysia could use undervalued exchange rate strategy to improve its trade balances with the United States and Singapore but not Japan.